Intracortical Inhibition in the Affected Hemisphere in Limb Amputation - Candido Santos, Ludmilla; Gushken, Fernanda; Gadotti, Gabriela Morelli; Dias, Bruna de Freitas; Marinelli Pedrini, Stella; Barreto, Maria Eduarda Slhessarenko Fraife; Zippo, Emanuela; Pinto, Camila Bonin; Piza, Polyana Vulcano de Toledo; Fregni, Felipe (Frontiers in Neurology, 2020)
Phantom limb pain (PLP) affects up to 80% of amputees. Despite the lack of consensus about the etiology and pathophysiology of phantom experiences, previous evidence pointed out the role of changes in motor cortex excitability as an important factor associated with amputation and PLP. In this systematic review, we investigated changes in intracortical inhibition as indexed by transcranial magnetic stimulation (TMS) in amputees and its relationship to pain. Four electronic databases were screened to identify studies using TMS to measure cortical inhibition, such as short intracortical inhibition (SICI), long intracortical inhibition (LICI) and cortical silent period (CSP). Seven articles were included and evaluated cortical excitability comparing the affected hemisphere with the non-affected hemisphere or with healthy controls. None of them correlated cortical disinhibition and clinical parameters, such as the presence or intensity of PLP. However, most studies showed decreased SICI in amputees affected hemisphere. These results highlight that although SICI seems to be changed in the affected hemisphere in amputees, most of the studies did not investigate its clinical correlation. Thus the question of whether they are a valid diagnostic marker remains unanswered. Also, the results were highly variable for both measurements due to the heterogeneity of study designs and group comparisons in each study. Although these results underscore the role of inhibitory networks after amputation, more studies are needed to investigate the role of a decreased inhibitory drive in the motor cortex to the cause and maintenance of PLP.